BANDWIDTH IN COMPUTER NETWORK CHANNELS. TERMS OF FREQUENCY-POWER BALANCE - Василенко, В. (Science-based technologies, 2010)
The terms of increase of carrying capacity are considered in dustings of computer networks on the basis of providing of terms frequency-power balance. As a variant of increase of carrying capacity is considered possi-bility of laying out of bar of key-in of channel.